Integrating social media marketing toward business performance and food truck business resiliency: a conceptual framework/ Hairul Nizwan Abd Majid ... [et al.] - Abd Majid, Hairul Nizwan; Mohd Zahari, Mohd Salehuddin; Jipiu, Lovelyna Benedict; Kutut, Mohd Zain; Bashir, Muhammad 'Arif Aizat (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Due to the rise of popularity of mobile food truck businesses and in line with the challenging food business realm, the efforts of improving the business performance and resiliency demand a more comprehensive view on the influence of its operational attributes towards customer acceptance. However, without prejudice, there is still no study specifically looking at the causes and effects of food truck attributes, mediating effect of customers' acceptance, and business performance toward its business resiliency. In fact, there is still a lack of studies centrally looking at the moderating effect of social media marketing on customers' acceptance of mobile food truck businesses. Understanding these issues is considered important not only for the changes in customer's food behavioural pattern, mobile food truck operator's business survival, but country economic contribution. This research note is an effort to understand the influence of the mobile food truck operational attributes and moderating effect of social media marketing toward its business performance and resiliency. Thus, a conceptual framework integrating social media marketing toward business performance and the mobile food truck business resiliency is proposed to fill the gap and align with the earlier issues.